African American and Mexican American Youths' College Adjustment and Perceptions of Parental Academic Socialization: Interactions Between Ethnicity and Parental Education. Issue 3 (2nd July 2016) - Suizzo, Marie-Anne; Pahlke, Erin; Chapman-Hilliard, Collette; Harvey, Kristin Emilia
Abstract : In a sample of 283 African American and Mexican American college students, we investigated the effects of ethnicity and parental education on three dimensions of parental academic socialization (PAS), active involvement, autonomy support, and demanding hard work, and their impact on college adjustment. Controlling for parental education, African Americans reported higher parental active involvement. Academic self-efficacy mediated the effects of both demanding hard work and autonomy support on college adjustment, controlling for parental education. Moderated mediation models suggested that effects of both demanding hard work and autonomy support on academic self-efficacy were stronger for African Americans than for Mexican Americans.